A near-infrared photoacoustic probe for specific detection of fluoride ion in vivo. (September 2022) - Xu, Na; Gao, Han; Wang, Sisi; Gai, Lizhi; Tian, Jiangwei; Shao, Xinxin; Lu, Hua
Abstract: Fluoride is an essential trace element in the human body and plays an essential role in various physiological processes. However, fluoride ion detection in vivo remains challenging due to the lack of probes that can enter the organism and emit at the near infrared region (NIR). Herein, we developed a boron-dipyrromethene (BODIPY)-based NIR probe that takes advantage of the high resolution and deep penetration of photoacoustic imaging, which can produce high NIR absorption at 803 nm in the presence of fluoride ions, resulting in a strong photoacoustic signal in the NIR region. In addition, the probe exhibits high selectivity for fluoride ions. In view of these outstanding features, the probe was then successfully applied to fluoride ion imaging in living mice, proving that a probe is a promising tool for fluoride ion detection in vitro and in vivo . Graphical abstract: Image 1 Highlights: A boron-dipyrromethene (BODIPY)-based NIR photoacoustic probe for fluoride ions was developed. The F − induced cleavage of Si–O bond results in a significant redshift to 803 nm. Imaging fluoride ions in living mice was successfully applied. This is the first photoacoustic probe of fluoride ions in the NIR region (700–900 nm).